(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Organisations that need to share sensitive data – medical records between hospitals, supply chain documents between manufacturers and auditors, financial records between regulators and banks – face a fundamental tension: the data must be accessible to authorised parties but invisible to everyone else, and the access rules must be enforced without relying on a single trusted intermediary. Traditional approaches – centralised data lakes with API gateways, federated identity brokers, encrypted file shares – place trust in the infrastructure operator, creating single points of compromise. Blockchain-based data sharing replaces that single trust point with cryptographic enforcement: access policies are encoded as smart contracts, data is encrypted with attribute-based or proxy re-encryption, and every access event is recorded on an immutable audit ledger. We present the Secure Data Sharing Architecture Framework (SDSAF), evaluating five blockchain-based sharing architectures – on-chain encrypted storage, off-chain storage with on-chain access control, proxy re-encryption networks, attribute-based encryption with smart contract policies, and confidential computing enclaves with blockchain attestation – across three enterprise workloads (healthcare record exchange, supply chain document sharing, regulatory reporting). Our Architecture Quality Score (AQS) measures confidentiality strength, access control granularity, throughput, latency, and regulatory compliance. Attribute-based encryption with smart contract policies achieves the highest AQS (0.908) by combining fine-grained cryptographic access control with on-chain policy enforcement, while proxy re-encryption networks achieve the lowest latency for cross-organisational sharing (340 ms per re-encryption delegation).